Penggunaan Model Pembelajaran Cooperative Learning Teknik Two Stay Two Stray (TSTS) Dalam Meningkatkan Prestasi Belajar - Naomi Fahma; Nur Rohmah Tunasikah (Teknodika, 2019)
This research is classroom action research consisting of two cycles and each cycleconsists four stages: planning, implementation, observation and reflection. The subjects of the research were 40 grade X students of AK 1 class in SMK  Muhammadiyah 1 Yogyakarta in the academic year of 2017/2018. The data collection techniques were observation, evaluation/ tests, and documentation. The data analysis technique used was quantitative data analysis. Based on the results of the research, in conclusion, the implementation of cooperative learning two stay two stray technique can improve the grade X students’ accounting learning achievement of AK 1 class in SMK Muhammadiyah 1 Yogyakarta. It was supported by the research data showing that the improvement of students’ learning achievement were obtained from the mean score of pre-test and post-test in Cycle I that was 20.63. In Cycle II, the mean score of pre-test and post-tense were improved 18,13. Besides, there were some improvement of students’ accounting learning achievement from Cycle I to Cycle that was proven by the increase of post test score 9.0 and the number of students who passed KKM from 82.50% to 100%